2020
DOI: 10.1097/ico.0000000000002279
|View full text |Cite
|
Sign up to set email alerts
|

Deep Neural Network-Based Method for Detecting Obstructive Meibomian Gland Dysfunction With in Vivo Laser Confocal Microscopy

Abstract: Purpose: To evaluate the ability of deep learning (DL) models to detect obstructive meibomian gland dysfunction (MGD) using in vivo laser confocal microscopy images. Methods: For this study, we included 137 images from 137 individuals with obstructive MGD (mean age, 49.9 ± 17.7 years; 44 men and 93 women) and 84 images from 84 individuals with normal meibomian glands (mean age, 53.3 ± 19.6 years; 29 men and 55 women). We constructed and trained 9 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Recently, artificial intelligence (AI) technology including deep learning (DL) has resulted in remarkable progress in medicine, and various applications for diagnostic imaging have been reported 15 . In the field of ophthalmology, many researchers, including the authors, have reported the performance of DL in image analysis using in vivo laser confocal microscopy, optical coherence tomography (OCT), OCT angiography, and ultra-wide-field fundus ophthalmoscopy 16 27 . Recently, Poplin et al reported that using machine-learning algorithms, cardiovascular risk factors including age can be predicted from retinal fundus photographs 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, artificial intelligence (AI) technology including deep learning (DL) has resulted in remarkable progress in medicine, and various applications for diagnostic imaging have been reported 15 . In the field of ophthalmology, many researchers, including the authors, have reported the performance of DL in image analysis using in vivo laser confocal microscopy, optical coherence tomography (OCT), OCT angiography, and ultra-wide-field fundus ophthalmoscopy 16 27 . Recently, Poplin et al reported that using machine-learning algorithms, cardiovascular risk factors including age can be predicted from retinal fundus photographs 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Automated image recognition using deep learning methods is becoming increasingly important in the decision making, planning, and execution of ophthalmic surgeries. While there are numerous studies on the retina, there are very few studies on the anterior eye segments, especially the cornea 17 , 18 . Nevertheless, it has been shown that artificial intelligence and image data obtained by OCT can be used to detect and classify certain corneal diseases, and even predict the probability of the need for future keratoplasty 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Automated image recognition using deep learning methods is becoming increasingly important in the decision making, planning, and execution of ophthalmic surgeries. While there are numerous studies on the retina, there are very few studies on the anterior eye segments, especially the cornea [14,15].…”
Section: Discussionmentioning
confidence: 99%